"New turns from old STaRs": Enhancing the capabilities of forensic short tandem repeat analysis. Issue 21 (16th July 2014) - Phillips, Christopher; Gelabert‐Besada, Miguel; Fernandez‐Formoso, Luis; García‐Magariños, Manuel; Santos, Carla; Fondevila, Manuel; Ballard, David; Syndercombe Court, Denise; Carracedo, Ángel; Victoria Lareu, Maria; McCord, Bruce
<x xml:space="preserve">Abstract</x> The field of research and development of forensic STR genotyping remains active, innovative, and focused on continuous improvements. A series of recent developments including the introduction of a sixth dye have brought expanded STR multiplex sizes while maintaining sensitivity to typical forensic DNA. New supplementary kits complimenting the core STRs have also helped improve analysis of challenging identification cases such as distant pairwise relationships in deficient pedigrees. This article gives an overview of several recent key developments in forensic STR analysis: availability of expanded core STR kits and supplementary STRs, short‐amplicon mini‐STRs offering practical options for highly degraded DNA, Y‐STR enhancements made from the identification of rapidly mutating loci, and enhanced analysis of genetic ancestry by analyzing 32‐STR profiles with a Bayesian forensic classifier originally developed for SNP population data. As well as providing scope for genotyping larger numbers of STRs optimized for forensic applications, the launch of compact next‐generation sequencing systems provides considerable potential for genotyping the sizeable proportion of nucleotide variation existing in forensic STRs, which currently escapes detection with CE.